Sweeping tsunamis - Spilsbury, Louise. frey50; Spilsbury, Richard, 1963- (Chicago, Ill. : Heinemann Library, 2010)
Volcanic eruptions, landslides, and underwater earthquakes can all cause tsunamis, deadly waves that can go unnoticed in the open water until the waves get close to shore. In this book that discusses the causes of tsunamis, you'll also learn how tsunamis are formed, what type of damage they do, and where some of the worst tsunamis in history occurred.
What is a tsunami? -- What causes a tsunami? -- Where do tsunamis happen? -- What happens in a tsunami? -- Case study: the Indian Ocean, 2004 -- Who helps when tsunamis happen? -- Case study: Japan, 1993 -- Can tsunamis be predicted? -- Can people prepare for tsunamis? -- Case study: Papua New Guinea, 1998 -- Can tsunamis be prevented? -- Sweeping tsunamis of the past.
Keywords: Tsunamis; Tsunamis -- Environmental aspects; Tsunamis; Tsunamis -- Environmental aspects